Hak Pekerja Peyandang Disabilitas Di Jawa Timur Perspektif Maslahah Mursalah - Muhammad Munir (Jurnal Istiqro, 2020)
Human Rights as basic rights that are inherently inherent in human beings with universal nature, need to be protected, respected, and maintained, so that the protection and human rights of vulnerable groups, especially persons with disabilities. Persons with disabilities also have the same right in employment opportunities to obtain welfare through equal employment opportunities without discrimination. Although the Government has paid attention to the rights of workers with disabilities at work including protection of accessibility, but unfortunately in reality these regulations do not work properly. People with disabilities are not unable to work but are not given the opportunity so they cannot work, persons with disabilities are not because of their will but it is God's will and does not mean they cannot do anything when there are disabilities who cannot see but they can walk, can hear , and so forth. Basically in the world of employment already has a legal umbrella, namely Law No. 13 of 2003 concerning Manpower, which in it regulates, all matters relating to labor in the time before, during, and after the work period. The law also regulates the rights and obligations of business actors, the State and workers / laborers. So in this case concerning the rights of persons with disabilities who have equality and equality with other humans, especially in terms of work. The author would like to further analyze the rights of persons with disabilities to obtain employment in terms of their benefit, namely using the Islamic legal method Maslahah Mursalah.